Temporal changes in fecal swine microbiome primarily reflect Salmonella Typhimurium challenge and poor sanitary housing conditions, even with functional amino acid supplementation - Brandão Melo, Antonio Diego; Alves da Cunha Valini, Graziela; Yang, Qinnan; Karpeggiane de Oliveira, Marllon José; Alves Marçal, Danilo; Righetti Arnaut, Pedro; França, Ismael; Alisson Silva, Cleslei; Korth, Nate; Pavlovikj, Natasha; Reis Furtado Campos, Paulo Henrique; Gastmann Brand, Henrique; et al. (Frontiers in Veterinary Science, 2025)
Nutrition has a significant impact on the gastrointestinal (GI) microbiome, which can influence pig metabolism, nutrient absorption, biomolecule synthesis, and bioavailability (including bile acids and short-chain fatty acids), as well as colonization resistance to GI pathogens and overall disease tolerance through immune maturation and regulation. The aim of this study was to assess the impact of functional amino acid supplementation on the fecal microbiome of pigs allocated into GOOD vs. POOR sanitary conditions (SC) over time, using 16S rRNA data. A total of 120 female growing pigs were randomly assigned in a 2 × 2 factorial arrangement (n = 30/treatment), consisting of two sanitary conditions (GOOD vs. POOR) and two diets [control (CN; 100% NRC, 2012) vs. supplemented with AA (Trp, Thr, and Met+Cys: Lys ratios increased to 20% higher than CN)]. Pigs were allocated to the GOOD SC group and were sham-inoculated, and the barn was kept clean, whereas pigs housed under POOR SC were challenged with Salmonella Typhimurium, in addition to the spreading fecal material from a commercial farm undergoing poor growth performance. Fecal samples were collected at day post-challenge (DPC) 0, 10, and 21, and extracted DNA was sequenced for 16S rRNA data analysis. Although alpha-diversity analysis revealed minor, statistically significant changes between groups, beta-diversity analysis demonstrated a significant separation between communities based on sanitary conditions at DPC 21. Accordingly, the most important taxa differentiating the two groups were the enrichment of the following taxa in the POOR group at DPC 21: Clostridium sensu stricto 1, Dorea, Intestinibacter, Lactobacillus, Romboutsia, Ruminococcus torques, Subdoligranulum, Terrisporobacter, and Turicibacter. Network and correlation structural analysis further revealed a sub-structuring of the data, with positive correlations forming in the POOR SC group: Sub-cluster 1 (Romboutsia, Turicibacter, Clostridium sensu stricto 1, Terrisporobacter, and Intestinibacter) and Sub-cluster 2 (Dorea, Subdoligranulum, Ruminococcus torques, Blautia, Holdemanella, and Solobacterium). In conclusion, temporal changes in the fecal swine microbiome of growing pigs reflected the S. Typhimurium challenge and poor sanitary status despite a dietary surplus of functional amino acids.